Targeting viral entry as a strategy for broad-spectrum antivirals - Mazzon, Michela (F1000Res, 2019)
The process of entry into a host cell is a key step in the life cycle of most viruses. In recent years, there has been a significant increase in our understanding of the routes and mechanisms of entry for a number of these viruses. This has led to the development of novel broad-spectrum antiviral approaches that target host cell proteins and pathways, in addition to strategies focused on individual viruses or virus families. Here we consider a number of these approaches and their broad-spectrum potential.